The Influence on Self Efficacy, Machiavelliane Traits, and Ethical Environment on Whistleblowing Intention - Reni Suwandi Ade Puspita,; Ayatulloh Michael Musyaffi,; Adam Zakaria, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to examine the influence of self efficacy, machiavellian traits, and ethical environment on whistleblowing intention in the context of academic dishonesty among accounting students at state and private universities in the Greater Jakarta area (Jabodetabek). Employing a quantitative approach, a questionnaire was distributed to 100 respondents selected based on Roscoe’s sampling method. The theoretical framework incorporates the Theory of Planned Behavior and the Theory of Prosocial Organizational Behavior. Data analysis was conducted using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results indicate that all variables self efficacy, machiavellian traits, and ethical environment positively and significantly influence whistleblowing intention. These findings suggest that enhancing students self efficacy and fostering a strong ethical environment can encourage them to report academic misconduct. This research contributes to the development of ethical policies and practices in educational institutions.